CONGDARDIR: AN INNOVATIVE TRADITIONAL GAME-BASED MEDIUM TO ENHANCE HIGH SCHOOL STUDENTS SELF-AWARENESS - Ananda, Seha; Setyaputri, Nora Yuniar; Puspitarini, Ikke Yuliani Dhian (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
This study aims to develop and examine the feasibility of a traditional game-based medium, derived from the game